The Concept of the Composing Saw-U Solo Klom-Naree Saam Chan - Srisakon, Prachakon (Journal of Fine and Applied Arts Khon Kaen University, 2023)
This research document is the partial completion of the research report on the creation of exercises to enhance the skills for a solo performance of Saw-U. The objective presentation the concept of solo Saw-U composition to apply for preparation before an advanced solo Saw-U performance skills to the students in Phichitpittayakom School by Buk Phrai Boek Thang (neoclassic styles) concept of composition regarding Assoc. Prof. Phichit Chaisaree’s expressing the yearning for liberty with loyalty to tradition. This research was conducted by applying a qualitative research methodology, including field studies, interviews, music notation, and documentary research. The results revealed that the composition of solo Saw-U ‘Klom-Naree Saam Chan’ was single phrase and reprise, so the composer applied by arranging the first phrase with Oad style (Thaang Oad), while the latter was Phan style (Thaang Punn). The Oad style is imploring slow utterance (pleasingly Uan); on the contrary, the Phan style is sublime teasing (Yao-Yae). In addition, the composer had added 8 features in the solo song, including departing fingering-trill (Phrom Chak), closed-fingering-trill (Phrom Pit), open fingering-trill (Phrom Pued), flickered-fingering (Phrom Sa-bad), hiccups (Phrom Sa-Euk), glissando up (Rud Sai Khuen), glissando down (Rud Sai Long), and conjugate the sound (Krathop Siang). These are the significant features the musicians should have to show their excellent skills in solo performance.